Pengaruh Kompensasi Dan Motivasi Terhadap Prestasi Kerja Karyawan PT Kimia Farma Apotek Unit Bisnis Tasikmalaya - Isti Sindrika Ekawati; Arga Sutrisna; Depy Muhamad Pauzy (EBISMAN eBisnis Manajemen, 2023)
This study aims to determine the effect of compensation on employee performance at PT Kimia Farma Apotek Tasikmalaya Business Unit. The research method used is a quantitative descriptive method with a sample of 79 people. The data analysis tool used in this research is path analysis. The results of this study indicate that compensation has a positive and significant effect on work performance. Employee motivation has a positive and significant effect on work performance. Compensation has a positive and significant effect on employee motivation, compensation through motivation does not have a significant effect on employee performance. This means that motivation is not able to mediate compensation for employee performance.